Dampak Pengungkapan Technological Capital dan Inovasi terhadap Nilai Perusahaan - Pane, Zulfikar Ikhsan; Romel, Lenra; Setyaningsih, Ratih Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study aims to examine the effect of technology implementation and innovation on company value by using technological capital disclosure as an alternative measurement. The aim is to expand previous studies and at the same time confirm technological capital disclosure as a measurement in the field of technology. by using 75 valid observation based on companies listed in Jakarta Islamic Index which consistent reporting from 2019 – 2023, it result technological capital disclosure and innovation positive significant to firm value. Its also confirm technological capital disclosure as technology measurement in accounting area.